Utilization of Snakehead Fish Meat for Increasing Kidney Function in Rat Experiencing Physiological Stress - Sunarno Sunarno; Hajar Sokmawati; Rully Rahadian (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Physiological stress for a long time can lead to impaired kidney organ function. Snakehead fish meat are known to contain important nutrients such as albumin, glutamine, glycine, cysteine, and various minerals that can improve kidney function. This study was conducted to examine and analyze the effect of snakehead fish supplementation in feed towards body weight, kidney weight, diameter and number of glomerulus in Wistar rats with physiological stress. This study used 20 male Wistar rats divided into 5 groups consisted of 1 control group (P0) and 4 treatment groups (P1: 5%, P2: 10%, P3: 15%, P4: 20%). The treatments were performed with 4 times repetition. This study used Completely Randomized Design (CRD). The variables measured were body weight, kidney weight, diameter and number of renal glomerulus. The data obtained were analyzed using Analysis of Variance (ANOVA) at 5% significance level and continued with Duncan test with 5% significance level. The results of this study were: the supplementation of snakehead fish with 20% of concentration can increase the body weight; concentration 10; 15; and 20% can increase the weight of the kidney; concentrations of 5%, 10%, 15%, and 20% can increase the glomerular diameter in Wistar rats with physiological stress. The supplementation of snakehead fish with concentration of 5% to 20% did not affect the number of glomerulus of Wistar rats with physiological stress. Results of this study is useful as information for people who study the mechanism of kidney repair due to physiological stress.